Aqueous stable luminescent perovskite-polymer composites. (June 2019) - Carrillo-Carrión, Carolina; del Pino, Pablo; Pelaz, Beatriz
Graphical abstract: Highlights: LHP NCs encapsulated in a matrix of an amphiphilic polymer yields composites of 1-2 μm. The LHP-PMA composites are stable in water for months, keeping their photoluminescence properties. The polymeric matrix prevents anion exchange and greatly enhances thermal stability. · Upon NIR excitation, the up-converted emission of the LHP NCs can excite co-encapsulated dyes. Abstract: The applicability of lead halide perovskites nanocrystals (LHP NCs) is limited by their structural lability in aqueous media or under high humidity levels. One of the most straightforward solutions is their entrapment in glass or salt matrixes. Here, we propose the use of the amphiphilic polymer poly-(isobutylene-alt-maleic anhydride)-graft-dodecyl (PMA), which has been widely used to provide nanoparticles with colloidal stability in aqueous media. The partial hydrolysis of the polymeric matrix allows the LHP NCs to maintain their photoluminescence properties for extended periods of time (months), both in solution and upon surface deposition. Moreover, the PMA-glass formation prevents anionic exchange processes in LHP NCs and increases their thermal stability in aqueous solution. Importantly, the inclusion of fluorophores covalently bonded to the polymer matrix allows for fluorophore-activation by the LHP NCs through energy transfer triggered by near-IR excitation.